2015
DOI: 10.1111/jfb.12721
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of natural reproduction of the Allis shad Alosa alosa in the River Rhine following re‐introduction measures

Abstract: After stocking with larvae from the Gironde-Garonne-Dordogne population, in 2013, three young-of-the-year Allis shad Alosa alosa, probably originating from natural reproduction, were documented for the first time in a period of nearly 100 years in the River Rhine. In 2014, a further increase was observed when 57 juveniles and eight adults were caught; seven of these eight adults were derived from stocking, indicating the success of stocking measures within the framework of the EU-LIFE project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Concerning allis shad, there is an ongoing stocking program (started in 2008) in the Rhine River (Germany) with juveniles coming from assisted reproduction of wild spawners from the Gironde-Garonne-Dordogne basin (France) [ 33 ]; http://www.lanuv.nrw.de/alosa-alosa/en/ . Monitoring in the Rhine River reported that spawners have been observed in the river for the first time in more than a half century in 2013 and 2014, while juveniles are commonly caught in the estuary since the beginning of the stocking program [ 101 ]. These promising results are in line with the results of the current correlative modelling approach and those of [ 28 ] in which the Rhine basin will be suitable for shads around 2100 under climate change scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning allis shad, there is an ongoing stocking program (started in 2008) in the Rhine River (Germany) with juveniles coming from assisted reproduction of wild spawners from the Gironde-Garonne-Dordogne basin (France) [ 33 ]; http://www.lanuv.nrw.de/alosa-alosa/en/ . Monitoring in the Rhine River reported that spawners have been observed in the river for the first time in more than a half century in 2013 and 2014, while juveniles are commonly caught in the estuary since the beginning of the stocking program [ 101 ]. These promising results are in line with the results of the current correlative modelling approach and those of [ 28 ] in which the Rhine basin will be suitable for shads around 2100 under climate change scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Within a monitoring program in the course of the EU-LIFE and EU-LIFE + projects involving the reintroductions of the allis shad (Alosa alosa) in the River Rhine, inter alia fish scale samples for molecular analyses were collected, to assess the project success (Hundt et al 2015). The allis shad is an anadromous fish within the family Clupeidae, which was formerly widespread throughout Western Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Residential populations of allis shad were likewise extinct in the Rhine ecosystem by the middle of the 20th Century [ 4 , 5 ] until their repatriation in the course of the EU-LIFE project “The reintroduction of Allis shad ( Alosa alosa ) in the Rhine system” (2007–2010) and the follow-on EU-LIFE+ project “Conservation and Restoration of the Allis shad in the Gironde and Rhine watersheds” (2011–2015). Within these projects, allis shad brood stock from a natural population in France were spawned in captivity and 10.66 million larvae reared in aquaculture facilities were released into the Rhine system, between 2008 and 2014 [ 6 , 7 ]. Adult shad first returned to spawn in the Rhine six years after the release of larvae in these waters [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within these projects, allis shad brood stock from a natural population in France were spawned in captivity and 10.66 million larvae reared in aquaculture facilities were released into the Rhine system, between 2008 and 2014 [ 6 , 7 ]. Adult shad first returned to spawn in the Rhine six years after the release of larvae in these waters [ 7 ].…”
Section: Introductionmentioning
confidence: 99%